Akurasi Pemeriksaan Polymerase Chain Reaction Menggunakan Primer IS6110 dan MPB64 untuk Mendeteksi Mycobacterium tuberculosis pada Spesimen Formalin-Fixed Paraffin-Embedded - Timotius Benedict Djitro; Faramitha Nur Izzaty; Nur Rahadiani (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2019)
BackgroundOne of the chalangges faced in controlling tuberculosis (TB) is the availability of a fast and precise diagnostictool. The current gold standard for diagnosis of TB is acid-fast bacterial culture. However, FFPE (formalin-fixedparaffin-embedded) tissues are not ammenable for culture and the time required makes this method impracticalfor many centers. PCR is an alternative rapid diagnostic tool, and can be used with FFPE tissues. PCR hasshown high sensitivity and specificity for detecting M.tuberculosis, however there has been reports of lesssensitivity and specificity when using FFPE specimens. This report aims to determine the accuracy of PCRdetection of M.tuberculosis using primer IS6110 and MPB64 on FFPE specimens.MethodsLiterature searches were carried out on the Pubmed, Scopus, Proquest, Springer Link and Cochranedatabases. Two journals were relevant to the clinical scenario, then a critical review is carreid out using theDiagnostic Study Appraisal Worksheet from the Center for Evidence-based Medicine, University of Oxford,2010.ResultsCurrently, the accuracy of PCR primer IS6110 and MPB is not satisfactory. Sensitivity ranges from 45.5-88.9%and specificity is between 88.1% - 100. This broad sensitivity range is probably caused by tissue volume andembedding process that can cause damages to the integrity of M.tuberculosis DNA.ConclusionPCR examinations using IS6110 and MPB64 primers can be used as confirmation tests in FFPE specimensdue to its high specificity value. Broad sensitivity values can produce significant false negatives if no otherexamination is used in conjunction with PCR in FFPE specimens.